الاعتماد المستندي لدى المصارف الاسلامية كآلية لترقية الصادرات في الجزائر - رشيد, فرجاني; نوفل, طليبة; شكري, بروبة (unuversity of eloued- جامعة الوادي, 2023)
"الملخص: قدمت هذه الدراسة لتحدید آلیة فتح الإعتمادات المستندیة لدى المصارف الإسلامیة وتوضح مفهومها الحقیقي وممارسة هذه المصارف للإعتمادات المستندیة، ولتحدید تنفیذ الإعتمادات المستندیة لدى المصارف الإسلامیة، بدًءا من فتح الإعتماد المستندي وحتى إغلاقه وتنفیذه، وأظهار مدى إلتزامها بالأحكام الشرعیة مقارنة بالقوانین الوضعیة، ومن حیث المشكلات التي تواجهها المصارف الإسلامیة عند فتحها للإعتمادات المستندیة وأثناء تنفیذها لهذه الإعتمادات. من بين أهم النتائج المتحصل عليها من خلال هذه الدراسة وهي كالآتي: - استنتجنا أن المصارف الاسلامية لا تتعامل بالربا كلــيا. - المصارف الاسلامية تقوم بالتنسيق بين أحكام الشريعة والأعراف الدولية المتعامل بها. - الاعتماد المستندي هو عبارة عن وسيلة تمضن حقوق المورد والمستورد. - العقد الذي يتم بين البائع والمشتري هو الأساس في عملية فتح الإعتماد." "Abstract This study has been prepared to establish the mechanisms for opening letters of credit in Islamic financial institutions and clarifying their actual rules and regulations, and for these institutions to put these regulations into practice. It will also show the steps needed to implement these letters of credit within Islamic financial institutions, starting with issuing the letter of credit until its completion, and to show their adherence to the Islamic laws in relations to prevailing civil laws. It will also address the problems that Islamic institutions face when they open letters of credit and during its. Among the most important results obtained through this study are as follows: - We concluded that Islamic banks do not deal with usury at all. - Islamic banks coordinate between the provisions of Sharia and international norms dealt with. - Documentary credit is a means that guarantees the rights of the supplier and the importer. - The contract between the seller and the buyer is the basis for the process of opening the credit."
Keywords: الإعتماد المستندی، المصارف الإسلامیة، القوانین الوضعیة; Documentary credit, Islamic banks, positive laws.